Sikap Berhubungan dengan Tindakan Adaptasi Kebiasaan Baru (AKB) Remaja - Rapotan Hasibuan (Jurnal Kesehatan Manarang, 2021)
The New Habit Adaptation (AKB) policy issued by Indonesian government is a form for implementing the new normal order during the COVID-19 pandemic, which has not been optimally implemented, especially for adolescents. Several studies and current observations showed that adolescents were still not adherent to implementing health protocols. This study, therefore, aims to analyze the link between knowledge, attitudes, and AKB adolescent practice in North Sumatra. A quantitative study with cross-sectional design was applied for this research involving 246 adolescents spread over 6 (six) working areas of Primary Health Care (Puskesmas) who was determined by purposive sampling. Data were collected using an online questionnaire which has been tested for validity and reliability, then data were analyzed descriptively by cross-tabulation and associatively by chi-square. The results showed the behavior of implementing AKB practice by adolescents was high (60.2%), knowledge was in the high category (92.7%) and adolescent attitudes were also positively supportive (90.7%). In addition, the significance test showed that there was a link between attitude and practice (p = 0.030; POR = 2.574). However, no link appeared to exist between knowledge and practice. This research contributes for developing of AKB policy outreach interventions by stakeholders and efforts to involve youth groups in the participatory achievement of AKB policy.